(3hSjdI GdeBd aj YO efGbH GdBds - (3CHh GdYHGS CMeO Hf GdaVd Hf eMeO HGcKjQ GdMVQej Gdecj GdTGaYj, HGcKjQ,J (B1047 (3g` s ((3GdMQe GdTQja s)
(3ChdgG (B:s
(3CeG HYO deG cGf ChKb eG JeSc GdEfSGf HSHHg eMHI Cgd HjJ GdfHi GdcQje CQOJ Cf CLeY ai Sdc JCdjai gPG bWQg ef HMQ aVGFdge GdTQjaI s
(3BNQgG (B:s
(3hcGf GdaQGZ ef LeY cJGHfG gPG ai GdSfI GdSGHYI hGdYTQjf HYO GdCda hdJeGeg eSc GdNJGe , hGddg JYGdi CYde s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B46s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B405 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B470 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs